2020
DOI: 10.1016/j.cgh.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Patients With Microscopic Colitis in Sweden

Abstract: BACKGROUND & AIMS: Microscopic colitis is one of the most common causes of chronic diarrhea in older populations. We investigated all-cause and cause-specific mortality in patients with microscopic colitis. METHODS: We conducted a nationwide cohort study of all cases of microscopic colitis (n [ 14,333) diagnosed from 1990 through 2017 in Sweden. Cases of microscopic colitis were identified using SNOMED codes from gastrointestinal histopathology reports collected from Sweden's 28 pathology departments. Each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…MC is frequently missed or confused with diarrhea‐predominant irritable bowel syndrome (IBS), and the symptoms can result in severe impairment in the quality of life. A nationwide cohort study in Sweden found that patients with MC were at increased risk of death with a 10‐year absolute risk difference of 3.4% compared with the population without MC, which may be to be due to a higher burden of comorbidities 76 . The incidence increases with age, with a peak incidence in sixth and seventh decades of life 77 .…”
Section: Microscopic Colitismentioning
confidence: 99%
“…MC is frequently missed or confused with diarrhea‐predominant irritable bowel syndrome (IBS), and the symptoms can result in severe impairment in the quality of life. A nationwide cohort study in Sweden found that patients with MC were at increased risk of death with a 10‐year absolute risk difference of 3.4% compared with the population without MC, which may be to be due to a higher burden of comorbidities 76 . The incidence increases with age, with a peak incidence in sixth and seventh decades of life 77 .…”
Section: Microscopic Colitismentioning
confidence: 99%
“…We have previously outlined our method for identifying MC cases in Sweden. [15][16][17] Briefly, we used the ESPRESSO (Epidemiology Strengthened by histoPathology Reports in Sweden) cohort, 18 a cohort of gastrointestinal histology from all 28 pathology departments in Sweden from January of 1965 until April of 2017. Each pathology report in ESPRESSO includes data on personal identity number, date of biopsy, anatomic location, and morphology according to the Systematized Nomenclature of Medicine (SNOMED) system (CC: M40600 and LC: M47170).…”
Section: Study Populationmentioning
confidence: 99%
“…While the morbidity of this condition is well understood and described, 5 there are scant data on its impact on mortality. In this month's Clinical Gastroenterology and Hepatology, Khalili and colleagues 6 address this knowledge gap with their prospective cohort study evaluating the risk of death in patients with microscopic colitis. The investigators matched each of 14,333 cases of microscopic colitis diagnosed in Sweden between 1990-2017 to 5 population comparators.…”
Section: Mortality Of Patients With Microscopic Colitis In Swedenmentioning
confidence: 99%